Assimilation Rights as a Right of Correctional Citizens: A View of the Indonesian Criminal Justice System - Mohammad Ashraff (IJCLS (Indonesian Journal of Criminal Law Studies), 2021)
The criminal justice system in Indonesia has the final stages in the criminal justice process. Correctional services in carrying out coaching for people convicted in the judicial system which previously adopted a prison system with the intention of making prisoners have a deterrent effect on what he did. Prisoners provide guidance in the correctional institution in accordance with the authority and main duties of the correctional institution, which provides services in the form of fostering people who are undergoing a criminal period to be accepted back into the community The inmates who carry out the guidance have a number of rights granted by the state. The guarantee for the granting of this right has been regulated in a formal legal instrument so that its implementation is a constitutional obligation. Correctional assisted residents have rights, one of which is assimilation. Assimilation is given as a commitment to the correctional model that is formed to achieve social reintegration. The function of a prisoner must be returned to the community in accordance with the ideals of the prison, namely so that the inmates can carry out socialization again to the community. Assimilation given has a number of terms and conditions that apply. At the coaching stage, assimilation is the final stage of coaching, to be ready to be released again and to process socially in the community.